Enunciação e humor : uma análise linguística de tiras - Schneider, Fernanda (2011)
In this study, we propose to analyze the construction of the humor in the strips of Iotti. Our main objective is to describe and analyze how the humor is built from the study of concepts proposed in the theory that guides this research. We take as a starting point for such research, the theoretical support in the works of Benveniste entitled Problems in General Linguistics I and Problems in General Linguistics II (1966 - 1974, respectively). Under the proposal made here, the enunciation of the order is unrepeatable, singular, manifested every time someone says "I" to a "you " for "he". From this theoretical context developed an argument in favor of that humor is the result of a construction derived from the situation of enunciation, understood from what Benveniste believes enunciation of "speech act of making the language" (FLORES; TEIXEIRA, 2008, p. 42). Thus, research is descriptive and qualitative bibliography because its purpose is to observe and analyze linguistic facts in comic strips. For that, we started with the notion that "the reference is part of the enunciation (BENVENISTE, 2006c, p. 84), is the announcer states that the act of speech. Since the reference - singular and unrepeatable meaning of the language - can not be predicted or determined, the assumption is that the humor is done in the speech situation - that is defining the reference through the inseparable relationship of form and meaning (semiotic and semantic). For the proposed objectives are achieved, we used a corpus consisting of five (5) strips of Iotti (2010), selected from the official website of the author. After selecting the corpus, we conducted an analysis of each strip into two stages: 1) the textual description of the strip, 2) analyzing expository Strip, considering the relationship enunciation and mood, based on three elements that, according to Benveniste (2006c) constitute the formal framework of enunciation: the act of enunciation: the situation where the announcement is made and the instruments used in language use in the strips analyzed. Then we proceeded to discuss the analysis. Through this study, we realized that it is the inseparable relationship between form and meaning that the humor is built on/and enunciation